STUDY OF THE EFFECT OF ETHANOL ADDITION AND SOLUTION HEATING ON THE DETERMINATION OF AMMONIA IN WATER BY INDOPHENOL BLUE METHOD - Hasri Hasri; Mudasir Mudasir (Indonesian Journal of Chemistry, 2002)
The effect of ethanol addition and solution heating on the analytical performance of the determination of ammonia in water by indophenol blue method was studied. The addition of ethanol and solution heating was intended to overcome the problem of reproducibility and sensitivity ussually found in the determination of ammonia by indophenol blue method which is carried out in 100 % aqueous media. The determination of ammonia was done indirectly by reacting ammonia in the sample with hypochloride and phenol using nitroprussida as catalyst to yield blue color-intense chromophore of indophenol. The chromophore was then detected by UV-Visible spectrophotometer. The proposed method was applied for the determination of ammonia in various samples of river water located in Yogyakarta and Makassar.             Results of the study showed that ethanol addition into analytical solution and solution heating enhanced the formation of indophenol blue. The optimal heating was achieved after 90 minutes of mixing. In ethanol/water medium (50/50, v/v), indophenol blue exhibited maximum absorbance at 648 nm. The analytical performance of ammonia determination by indophenol blue method in this medium is as followed: detection limit = 0.03 ppm, relative standard deviation (RSD) = 2.50 % and the calibration curve was linear in the concentration range of 0.0 - 0.4 ppm with correlation coefficient (r) = 0.9968. Results of ammonia determination in various samples of river water showed that the highest concentration of ammonia (2.421 ppm) was found in Tallo river, Makassar, while the lowest (0.359 ppm) was shown by the river near SGM factory, Yogyakarta.